Machining and CNC technology (sách photo) - Fitzpatrick Michael (American : MC Graw Hill, 2005)
This is an introductory machine tools text that assumes students have had no previous machining instruction. Students will learn good machining principles and CNC operations that all machine tools now have as standard equipment. The content of this text fits any equipment and supports any career plan.
Table of contents
Part 1: Introduction to manufacturing
Part 2: Introduction to machining
Part 3: Introduction to computer numerical control machining
Part 4: Advanced and advancing technology
Keywords: CNC technology; Machine - tools - Numerical control - Handbooks, manuals